2022
DOI: 10.1186/s40561-022-00220-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Master’s students’ academic performance: an empirical study in Germany

Abstract: The tremendous growth in electronic educational data creates the need to have meaningful information extracted from it. Educational Data Mining (EDM) is an exciting research area that can reveal valuable knowledge from educational databases. This knowledge can be used for many purposes, including identifying dropouts or weak students who need special attention and discovering extraordinary students who can be offered lifetime opportunities. Although former studies in EDM used an extensive range of features for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…No Approach Paper 1 Academic Performance Prediction [11], [12], [17], [18], [23], [24], [35], [37], [38], [41], [44], [45], [51], [56], [57], [64], [71], [74], [75], [78], [80], [81], [84] 2 At-Risk Student Prediction [1], [9], [10], [13], [19], [36], [50], [55], [59], [62], [65], [66], [73], [77], [79], [82] 3 Dropout/Graduation Prediction [14], [15], [20], [21], [47], [48], [54], [60], [61], [63], [72],…”
Section: Table 4 Mapping Of Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…No Approach Paper 1 Academic Performance Prediction [11], [12], [17], [18], [23], [24], [35], [37], [38], [41], [44], [45], [51], [56], [57], [64], [71], [74], [75], [78], [80], [81], [84] 2 At-Risk Student Prediction [1], [9], [10], [13], [19], [36], [50], [55], [59], [62], [65], [66], [73], [77], [79], [82] 3 Dropout/Graduation Prediction [14], [15], [20], [21], [47], [48], [54], [60], [61], [63], [72],…”
Section: Table 4 Mapping Of Approachesmentioning
confidence: 99%
“…The prompt identification of students' academic performance is widely recognized as a vital asset for enhancing the quality of education [71]. Researchers are showing interest in predicting academic performance, this can be seen from increasing numbers of research on predicting academic performance as well as selected primary publications stating that it is beneficial to students [23], [24], [35], [44], [45], [51], [71], [74], [78], [80], [84], instructors [11], [12], [17], [18], [23], [24], [37], [38], [41], [44], [45], [57], [64], [75], [78], educational institutions [17], [23], [24], [37], [78]. From the discussion above, it can be concluded that there are several objectives behind predicting academic performance:…”
Section: Table 4 Mapping Of Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the tenets of SLT, social circles act as crucibles wherein individual competencies and skills predominantly emerge [ 31 ]. Further advancing this argument, previous research explicates that external circumstances and peer influences significantly shape learning outcomes [ 32 ].…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Further advancing this argument, previous research explicates that external circumstances and peer influences significantly shape learning outcomes [ 32 ]. Moreover, this theoretical lens delves into the interplay between intellectual and environmental stimuli in molding both attitudinal and learning dispositions [ 31 ]. In this context, learning is conceptualized not as an isolated endeavor, but as a collaborative social activity.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%